Francisco Moreno Fernández, Sociolingüística cognitiva. Proposiciones, escolios y debate. Iberoamericana-Vervuert, Madrid, 2012; 302 pp. - Ivanova, Olga; Bartol, José Antonio (El Colegio de México, 2014)
Se hace una reseña del libro Sociolingüística cognitiva. Proposiciones, escolios y debate.